Is Vitamin D Testing in the Hospitals of Peshawar Consistent with Guideline Recommendations? - Ambreen Ali, Maria Tasneem Khattak, Kanwal Nazir Arbab, Nayab Sarwar, Saad Ali Khan, Mohibullah Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Vitamin D is a prohormone that has been shown to impact immune response and is well-known for its role in bone health. An expanding body of evidence suggests that 25OHD testing is being misused, which causes a heavy burden on the healthcare system. Analysis of all serum 25OHD tests given to adult inpatients and outpatients from January 1, 2022 through March 1, 2022. It was determined that a total of 189 tests were conducted during the audit period of one week. There were 130 preliminary examinations, 40 of which were conducted on individuals already receiving vitamin D supplementation. The number of people who had a valid reason to get tested (55) was significantly higher than those who did not (23). Fifty-one percent of the 183 25OHD tests were unnecessary. A reduction in testing may be possible if current recommendations are strictly adhered to. Only 3% of individuals with vitamin D deficiency were tested for celiac disease within nine months. Significant cost savings are achieved without compromising patient outcomes by increasing compliance with guide suggestions for 25 hydroxyvitamin D testing, utilization of test data, and implementation of recent reasons for examination. Possible causes of unneeded retesting include the lack of usage of electronic records and inadequate communication between doctors. It is possible that outcomes are not being actively studied due to a lack of distinguishable follow-up testing for vitamin D-related disorders.